SYNTHYSIS OF RAYON FROM DATE PALM FRONDS - & et al., Mahdi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The artificial silk (Rayon) was produced from the fronds of date palms which was taken from date palm trees (type Al-Zahdi) from the Iraqi gardens. Two main parts of the frond, namely leaves and stalks were used in this study to produce rayon. The palm fronds were converted into a powder of 90-180 micrometers. Major steps were used to produce rayon; delignification, bleaching and finally dissolution. Modified organosolv method which uses organic solvent method was applied to remove high lignin content. Three variables were studied in the delignification process: temperature, the ratio of ethanol to water and digestion time. The results showed that the best percent of lignin removal was (97%) which occured at; digestion time (80 minutes), temperature (185oC) and the ratio of ethanol: water of 50: 50 wt/wt. Statistical experimental design type Central Composite Design (CCD) has been used to find a mathematical relationship between the variables and the remaining lignin percent as a dependent variable.  The effect of using different catalysts in delignification process  have been studied and found that the best catalyst is sodium hydroxide at the concentration (0.025) mole/L which gave the same percent removal of lignin (97%) but with low digestion time about 30 min. In the next step, the cellulose was dissolved using. NaOH with different concentrations (4%-12%) and the results showed that the optimum concentration of sodium hydroxide was 8% at temperature - 20oC. In order to improve cellulose dissolution, urea was added with proportion (6% NaOH + 4% urea). Finally, the cellulose was spinning with 10% H2SO4 to prepare rayon.